A systematic literature analysis of influencing factors affecting the balance between usability and emotional product design - van Remmen, Judith Sophie; Wartzack, Sandro; Miehling, Jörg (Journal of Engineering Design, 2025)
In today's competitive market, successful product development hinges on understanding user needs and experiences. With the proliferation of expanding technologies like the Internet of Things, developers can gather vast amounts of data about user interactions. To leverage this wealth of information effectively, a user-centred approach to product development is imperative. This paper explores the convergence of usability and emotional design in product development, examining their interplay and impact on user experience. Through a review of existing literature, it investigates influential factors shaping the prioritisation of usability and emotional design elements. Key questions addressed include identifying these influential factors, assessing their impact on usability and emotional design, and elucidating their interrelationships. By shedding light on these dynamics, this systematic review aims to inform product developers and designers, facilitating the creation of products that resonate with users on both usableand emotional level
Keywords: User-centred design; product design; usability; emotional product design; review